2016
DOI: 10.5194/amt-9-5523-2016
|View full text |Cite
|
Sign up to set email alerts
|

Inferring <sup>222</sup>Rn soil fluxes from ambient <sup>222</sup>Rn activity and eddy covariance measurements of CO<sub>2</sub>

Abstract: Abstract. We present a new methodology, which we call Single Pair of Observations Technique with Eddy Covariance (SPOT-EC), to estimate regional-scale surface fluxes of 222 Rn from tower-based observations of 222 Rn activity concentration, CO 2 mole fractions and direct CO 2 flux measurements from eddy covariance. For specific events, the regional ( 222 Rn) surface flux is calculated from short-term changes in ambient ( 222 Rn) activity concentration scaled by the ratio of the mean CO 2 surface flux for the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…In particular, some SBFs from the N‐NE (15°–45°) induce a significant increase only at 20 m (Figure e), whereas they lead to decreases at 200 m. Furthermore, one SB event from the N‐NW (315°–345°) induces a large jump (∼ 1 Bq/m 3 ) at both 20 and 200 m agl. There is also a single event from the W‐SW, marked in this case by a significant fall in 222 Rn of more than 1 Bq/m 3 at 20 m and of around 0.5 Bq/m 3 at 200 m. These observations disagree with the estimates of van der Laan et al () for the surface fluxes of 222 Rn, and must therefore be explained by processes other than nearby emissions. First, the increase in wind speed enhances the dilution of 222 Rn and consequently produces a fall of its concentration (Ho and Measday, ; Vargas et al ), but, on the other hand, the transition from convective to stably stratified conditions builds up 222 Rn at lower levels.…”
Section: Impact On Scalar Transportcontrasting
confidence: 53%
“…In particular, some SBFs from the N‐NE (15°–45°) induce a significant increase only at 20 m (Figure e), whereas they lead to decreases at 200 m. Furthermore, one SB event from the N‐NW (315°–345°) induces a large jump (∼ 1 Bq/m 3 ) at both 20 and 200 m agl. There is also a single event from the W‐SW, marked in this case by a significant fall in 222 Rn of more than 1 Bq/m 3 at 20 m and of around 0.5 Bq/m 3 at 200 m. These observations disagree with the estimates of van der Laan et al () for the surface fluxes of 222 Rn, and must therefore be explained by processes other than nearby emissions. First, the increase in wind speed enhances the dilution of 222 Rn and consequently produces a fall of its concentration (Ho and Measday, ; Vargas et al ), but, on the other hand, the transition from convective to stably stratified conditions builds up 222 Rn at lower levels.…”
Section: Impact On Scalar Transportcontrasting
confidence: 53%
“…The Cabauw site (51.97 • N, 4.93 • E) is situated 32 km east of the centre of Rotterdam and is considered a semi-urban site (van der Laan et al, 2016;Vermeulen et al, 2011). This means the sampled air masses are influenced by urban emissions, but less often than a truly urban Laan et al, 2009aLaan et al, , 2016. These four stations together describe a transect from the city towards rural areas.…”
Section: Study Area and Measurementsmentioning
confidence: 99%
“…On average the CO 2 mixing ratios are similar at all levels during well-mixed daytime conditions (Vermeulen et al, 2011), but a large gradient is observed for stable conditions when the 20 m level is highly affected by surface fluxes surrounding the tower. Similarly, Turnbull et al (2015) suggested that measurements closer to the surface are more sensitive to local fluxes, and therefore a higher level than 20 m is more suitable to obtain information on more remote fluxes. We choose the 60 m level observations to be able to compare them easily to the Lutjewad site.…”
Section: Study Area and Measurementsmentioning
confidence: 99%
See 2 more Smart Citations